Pola Penggunaan Insulin terhadap Pasien Diabetes Mellitus Tipe 1 di Instalasi Farmasi Rawat Jalan Rumah Sakit X - Viny Megita Trivanka; Wempi Eka Rusmana (Jurnal Health Sains, 2021)
Type 1 diabetes mellitus is a condition characterized by high levels of sugar or glucose in the blood. This study aims to get an idea of the Pattern of Insulin Use In Patients with Type I Diabetes Mellitus installed Hospital Outpatient Pharmacy X. This study is a descriptive study. With retrospective research design. The data used is data that already exists in Hospital Pharmacy Installation X period of March 2021 as many as 82 patients. Pattern of Insulin Use Of Type I Diabetes Mellitus Patients in Hospital X period March 2021, Outpatients who were given the most insulin therapy based on female sex 43 patients (52.43%), based on the age of patients at most age range 51-60 as many as 28 patients (31.70%), based on the type of insulin used the most is rapid-acting as much as 44 (53.65%),  Then followed by long-acting as much as 19 (23.17), premixed as much as 18 (21.95) and combination of rapid acting and long acting as much as 9 (10.97%).